UPAYA MENINGKATKAN KEDISIPLINAN ANAK MELALUI METODE BERCERITA DENGAN BONEKA TANGAN - R Tita Fauziah; Budi Ilham Maliki; Amat Hidayat (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2024)
Discipline is a crucial aspect in forming a child's character, especially at an early age. This research aims to describe efforts to improve children's discipline through the application of the storytelling method with hand puppets. This method was chosen because the interactive and interesting storytelling approach is expected to convey disciplinary values in a way that is easy for children to understand. This research uses a descriptive qualitative approach, with research subjects consisting of group B students at Ar-Rofah Kindergarten, Baros sub-district, Serang Regency. Data was collected through direct observation of children's behavior during storytelling activities, interviews with teachers and parents, and analysis of activity documentation. The research results show that the method of telling stories using hand puppets contributes positively to increasing children's discipline, especially in terms of compliance with rules, listening to instructions, and regularity in daily activities. Children seemed more interested and focused during storytelling activities, which resulted in their more disciplined behavior in class. These findings indicate that the storytelling method using hand puppets can be an effective strategy in supporting the disciplinary development of early childhood.